2017
DOI: 10.1063/1.4979013
|View full text |Cite
|
Sign up to set email alerts
|

Analogue of ultra-broadband and polarization-independent electromagnetically induced transparency using planar metamaterial

Abstract: In this paper, a classical analogue of electromagnetically induced transparency (EIT) metamaterial is numerically and experimentally demonstrated. The unit cell of our proposed structure is composed of two identical and orthogonal double-end fork (DEF) metallic resonators. Under the excitation of the normally incident waves, each of the two DEFs exhibits different frequency of electric dipole response, which leads to the ultra-broadband and polarization-independent EIT-like effect. The resonant feature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…In addition, our designed structure is twodimensional and refers only to a single-layer metal surface, which is easily fabricated by utilizing the printed circuit board (PCB) technology. 20,23,25,26 Moreover, the transverse electric size of our structure is smaller ($0.28 l  0.16 l) and its thickness is lower ($0.018 l) as compared to that of the structure reported in ref. 25 (0.43 l  0.43 l  0.027 l).…”
Section: -28mentioning
confidence: 47%
See 1 more Smart Citation
“…In addition, our designed structure is twodimensional and refers only to a single-layer metal surface, which is easily fabricated by utilizing the printed circuit board (PCB) technology. 20,23,25,26 Moreover, the transverse electric size of our structure is smaller ($0.28 l  0.16 l) and its thickness is lower ($0.018 l) as compared to that of the structure reported in ref. 25 (0.43 l  0.43 l  0.027 l).…”
Section: -28mentioning
confidence: 47%
“…27 In our simulation, CST Microwave Studio soware was used. 27 Plane waves are incident perpendicular to the metamaterial surface, 26 with the E-eld polarized along the x-axis and H-eld polarized along the y-axis.…”
Section: Structure Designmentioning
confidence: 99%
“…It is evident from Figure 3a,c that the tunable PIT effect is identical for both the x-and y-polarized incident waves. Owing to its fourfold symmetry [40,41], the proposed PIT structure has an identical response for any incident polarization. This behavior can be explained by the fact that an arbitrarily polarized wave can be orthogonally decomposed into x-direction and y-direction polarized waves.…”
Section: Resultsmentioning
confidence: 99%
“…The EIT effect in MMs has been realized in planar structures comprising metal strips, coupled split ring resonators, etc. in the gigahertz [27][28][29][30][31][32] as well as terahertz [33][34][35][36][37] regime. Several studies have also been reported on the dynamic tuning of the EIT effect through the incorporation of non-linear media or semiconductor materials [34][35][36][37][38] at the unit cell level of the MM structures.…”
Section: Introductionmentioning
confidence: 99%